Development of Nature Tourism Innovations with Cultural History Sites Through Sport Tourism (Kayaking) and Based Ecotourism ProgramsDigitization-Android in Simawang District - Zulbahri; Dedi Supendra; Weny Sasmitha; Kamal Firdaus (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2023)
Another problem faced by the tourism management community in the Simawang district is the lack of knowledge and expertise in tourism management, both in terms of administration, organization and management of existing facilities and infrastructure. The lack of insight and knowledge of the tourism management community in IT development also has an impact on the lack of tourism promotion through social media that is currently developing. The solution to overcome these problems is by implementing a program to increase the insight and knowledge of the tourism management community related to management, administration, promotion, marketing and the ability to use IT. In addition, the solution provided is also in terms of increasing the quality and quantity of tourist objects from existing natural and regional potentials, namely through the development of sport tourism, such as water sports using kayaking. This community service or partnership activity includes; participant recruitment, implementation of training activities, coaching, guidance and development of activities using the Participation Actions Learning System (PALS) method, real development by tourism managers through partner participation in training and coaching and activity evaluation.